Social Research Applied to English Language Teaching in Colombian Contexts: Theory and Methods. Wilder Escobar (Ed.), Bogotá, Colombia: Universidad el Bosque, 2015, 187 pages. ISBN: 978-958-739-028-5 - Ortega, Yecid (Colombian Applied Linguistics Journal, 2016)
For decades, many researchers and teachers in the field of English Language Teaching (ELT) have acknowledged the challenges of bridging the gap between research and practice (Belcher, 2007; Korthagen, 2007). These are challenges for both teachers (e.g., technical language used in research) and researchers (e.g., lack of pedagogical implications for teachers). Wilder Escobar, editor of the book Social Research Applied to English Language Teaching in Colombian Contexts: Theory and Methods, attempts to address these challenges and invites authors to offer readers practical applications in ELT.